Colonic interposition for recurrent Gastroesophageal junction adenocarcinoma of stomach: a case report - Regmee, Sujan; Kharel, Shrijan; Bohara, Tanka Prasad; Joshi, Mukund Raj (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Gastric cancer is a major cause of cancer death worldwide. Potential curative treatment for gastric cancer is radical gastrectomy. The reasons for local recurrence could be many like inadequate margin at the time of resection, biology of the disease, bad patient compliance. Esophagogastrectomy with colonic interposition may be required in case of distal esophageal carcinoma, carcinoma of proximal stomach and also in esophagogastric anastomotic recurrence, especially when the stomach is not suitable or available.Case description: A 30-year-old female, who had undergone proximal partial gastrectomy about 14 months back for poorly differentiated mucinous adenocarcinoma of stomach, was admitted with a 20 days history of dysphagia which was initially for solid food but later progressed causing difficulty in swallowing liquid as well. In past 14 months patient had undergone 6 cycles of chemotherapy.  Transhiatal esophagectomy with interposition of right colon with terminal ileum with end to end anastomosis of oesophagus and ileal ends followed by colojejunostomy and ileocolostomy with FJ placement.Conclusion: When enough stomach remains it can be used as an esophageal replacement. However, when the stomach cannot be used due to more extensive primary disease or like in this case, needs to be resected due to recurrence of the disease, the interposed colon or jejunum needs to be used for esophageal reconstruction.